THE SURFACE MAGNETIC CHARGE INDUCED BY A HIGH-FREQUENCY WHISPERING GALLERY WAVE ON A SPHERICAL CAP WITH NONVANISHING FACE IMPEDANCES - SENGOR, T (AMER GEOPHYSICAL UNION, 1993)
We obtained the explicit expressions related to the scattering of the normal magnetic component of whispering gallery (WG) modes by a spherically curved sheet with different face impedances. For nonvanishing face impedances we have equivalent surface magnetic charge induced by the modes on the sheet. The results explain the influence of certain impedance properties of the diffraction of WG modes in a quite simple form. The analysis is based on one of the basic postulates of the Geometrical Theory of Diffraction, which describes high-frequency diffraction as a local phenomenon. When the radius of the sphere becomes infinitely large, the expressions are reduced to those of the classical half plane problems.
Keywords: HALF-PLANE; DIFFRACTION; Astronomy & Astrophysics; Geochemistry & Geophysics; Meteorology & Atmospheric Sciences; Remote Sensing; Telecommunications